Characterization and Identification of the Chemical Constituents of Gynostemma pentaphyllum Using High Performance Liquid Chromatography – Electrospray Ionization – Quadrupole Time-of-Flight Tandem Mass Spectrometry (HPLC-ESI-QTOF-MS/MS). (23rd March 2020) - Ling, Yun; Lei, Zhineng; Xinying Li; Yan, Xinyu; Siying Wang; Yang, Wanling; Nie, Qianhui; Zhang, Qing; Hai'ou Bao; Yu, Jingmou; Jin, Hongguang
Abstract: Gynostemma pentaphyllum has gained increasing interest in recent years for its widespread use as a medicinal plant, dietary supplement, herbal tea, and vegetable in China. This herb possesses many beneficial functions, such as anti-tumor, anti-inflammatory, cholesterol lowering, strengthening of the immune system, and blood pressure regulating activities. However, due to an absence of information, the major material components of Gynostemma pentaphyllum remain unknown. A method for the comprehensive profiling of components in Gynostemma pentaphyllum is reported using high performance liquid chromatography – electrospray ionization – quadrupole time-of-flight tandem mass spectrometry (HPLC-ESI-QTOF-MS/MS) in this study. As a result, a total of 36 compounds including flavonoid glycosides and gypenosides were characterized or tentatively identified. Four gypenosides were tentatively identified as potentially new compounds in Gynostemma pentaphyllum . These results provided a reference for comprehensive characterization of ingredients in Gynostemma pentaphyllum and are significant for the utilization of Gynostemma pentaphyllum .